2020
DOI: 10.1111/1749-4877.12492
|View full text |Cite
|
Sign up to set email alerts
|

Toxin variation among salamander populations: discussing potential causes and future directions

Abstract: Amphibians produce defensive chemicals which provide protection against both predators and infections. Within species, populations can differ considerably in the composition and amount of these chemical defenses. Studying intraspecific variation in toxins and linking it to environmental variables may help us to identify the selective drivers of toxin evolution, such as predation pressure and infection risk. Recently, there has been a renewed interest in the unique toxins produced by salamanders from the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(271 reference statements)
0
1
0
Order By: Relevance
“…Environmental variations can impose pressures on an animal’s physiology [ 1 , 2 , 3 ], phenology [ 4 , 5 , 6 ], morphology [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], distribution [ 20 ], and life-history strategies [ 21 , 22 , 23 , 24 , 25 , 26 ]. The ecogeographic patterns of covariation between biological traits and environmental variables [ 27 ] provide opportunities to assess the adaptions of animals in response to the selection pressures imposed by significant variations in temperature, precipitation, and associated microclimate variations [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental variations can impose pressures on an animal’s physiology [ 1 , 2 , 3 ], phenology [ 4 , 5 , 6 ], morphology [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], distribution [ 20 ], and life-history strategies [ 21 , 22 , 23 , 24 , 25 , 26 ]. The ecogeographic patterns of covariation between biological traits and environmental variables [ 27 ] provide opportunities to assess the adaptions of animals in response to the selection pressures imposed by significant variations in temperature, precipitation, and associated microclimate variations [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…amphibians, which overwhelmingly exhibit female-biased sexual size dimorphism (Shine, 1979;Lindenfors et al, 2007;Mori et al, 2017;Pogoda and Kupfer, 2018). A defining trait of amphibians is the presence of poison glands, but few studies have evaluated whether or not toxin phenotypes are sexually dimorphic (Mebs and Pogoda, 2005;Daly et al, 2008;Saporito et al, 2010;Stokes et al, 2011;Jeckel et al, 2015;Preißler et al, 2019;De Meester et al, 2021). Previous evaluations have focused on poison gland morphology and arrangement (Aoto, 1950;Staub and Julie, 1997;Chen et al, 2017;Zamora-Camacho, 2022) without addressing sexbased differences (Mailho-Fontana et al, 2019) and the few studies that have addressed poison composition and quantities found that anurans (family Dendrobatidae) exhibit sex-based differences due to diet (Saporito et al, 2006;Daly et al, 2008;Saporito et al, 2010;Jeckel et al, 2015).…”
mentioning
confidence: 99%
“…Previous evaluations have focused on poison gland morphology and arrangement (Aoto, 1950;Staub and Julie, 1997;Chen et al, 2017;Zamora-Camacho, 2022) without addressing sexbased differences (Mailho-Fontana et al, 2019) and the few studies that have addressed poison composition and quantities found that anurans (family Dendrobatidae) exhibit sex-based differences due to diet (Saporito et al, 2006;Daly et al, 2008;Saporito et al, 2010;Jeckel et al, 2015). In addition, urodeles (genus Salamandra) possess, overall, a similar alkaloid composition (Preißler et al, 2019), but show distinct quantities of component toxin between sexes (Mebs and Pogoda, 2005;De Meester et al, 2021).…”
mentioning
confidence: 99%